Law enforcement agencies of Ukraine: definition and functions - Бородін, Денис Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article presented for publication is the attempt to point out the problems of defining the notions of «law enforcement bodies», «functions of law enforcement bodies». In the paper the attention is paid to their theoretical and practical significance in the context of law-making process and organization of work of law enforcement agencies in Ukraine. The author mentions that a reforming process of society and state bodies is taking place in Ukraine. One of its tasks is to update a law enforcement agencies’ system. However there are no determined criteria for any state body to be recognized as a “law enforcement” one. That is why definition of such a criteria, establishment and understanding of law enforcement agencies’ functions, their place and role in the mechanism of ensuring the rights, freedoms and legal interests of persons is extremely urgent and important. The author gives the definition of law enforcement agency and states that it is a state body which performs one or few law enforcement functions and has a separate material and technical supplement of its employees. It’s also mentioned that legislation provide special requirements to this organ and its staff own specific rights and obligations.